Respuesta :
Answer:
[tex] \huge{ \boxed{36 {x}^{3} - \frac{6 {x}^{2} }{ \sqrt{x} } - 12x \sqrt{x} + 2 \sqrt{x} }}[/tex]
Step-by-step explanation:
To find the derivative of the function [tex](3 {x}^{2} - \sqrt{x} )^{2} [/tex] , the chain rule can be applied.
- First let's define the function as [tex] f(x) = (3 {x}^{2} - \sqrt{x} )^{2} [/tex]
- Next, the function can be rewritten as f(x) = u(x)² , where [tex] u(x) = (3 {x}^{2} - \sqrt{x})[/tex]
According to the chain rule, the derivative of f(x) with respect to x is given by:
[tex] \dfrac{df}{dx} = \dfrac{df}{du} \times \: \dfrac{du}{dx} [/tex]
where
[tex] \dfrac{df}{du} [/tex] represents the derivative f(x) with respect to u.
- Since f(x) = u(x)² , it can be differentiated as:
[tex] \dfrac{df}{du} = 2u(x)[/tex]
- Next we differentiate [tex] u(x) = (3 {x}^{2} - \sqrt{x}) [/tex] which is given as:
[tex] \frac{du}{dx} = \frac{d}{dx} ( {3x}^{2} ) - \frac{d}{dx} ( \sqrt{x} ) \\ \\ \frac{du}{dx} = {6x} - \frac{1}{2 \sqrt{x} } [/tex]
- Next we substitute the calculated values back into the chain rule formula given above, we have:
[tex] \frac{df}{dx} = 2u(x) \times (6x - \frac{1}{2 \sqrt{x} } ) \\ [/tex]
- Lastly we substitute [tex] u(x) = (3 {x}^{2} - \sqrt{x}) [/tex] back into the equation and simplify:
[tex] \frac{df}{dx} = 2(3 {x}^{2} - \sqrt{x} ) \times (6x - \frac{1}{2 \sqrt{x} } ) \\ = (6 {x}^{2} - 2 \sqrt{x} )( 6x - \frac{1}{2 \sqrt{x} } ) \\ = 36 {x}^{3} - \frac{6 {x}^{2} }{ \sqrt{x} } - 12x \sqrt{x} + 2 \sqrt{x} [/tex]
We have the final answer as
[tex]36 {x}^{3} - \frac{6 {x}^{2} }{ \sqrt{x} } - 12x \sqrt{x} + 2 \sqrt{x} [/tex]